AN ANALYSIS OF STUDENTS' DIFFICULTIES IN USING ENGLISH INTONATION AT GRADE EIGHT OF SMP NEGERI 2 PEMATANGSIANTAR - Purba, Christian Neni; Herman (Wiralodra English Journal, 2020)
This research is about the students’ difficulties in using English intonation. Since English is a foreign language, students always face problems especially in pronouncing the words. Pronouncing also refers to the intonation in conversation. Problem stated in this research as follow: What are the students’ difficulties in using English intonation? It focuses on the students’ intonation in a conversation, which consists of rising tone, falling tone and level tone. To answer the problem above, this research follows some theories, namely: Allen (1954), Hay craft (1971), Jones (1979), and Roach (2000). The research design is qualitative research. The subjects of this study are the second year students of SMP Negeri 2 Pematangsiantar, and the object is the student’s intonation. The technique of collecting data follows audio method or what is called recorded voice data. The data is analyzed by drawing the terminal contour of students’ intonation. The result of this research was there are three difficulties of students in using English intonation, namely: (1). Difficulty in using level tone, (2). Difficulty in using rising intonation (3). Difficulty in using falling intonation. This research finding recommends both teacher and students to take responsibility in overcoming those difficulties. An English teacher should teach his beginner students the using of intonation and its function in every kinds of sentence. Since there is an imitation process in learning intonation, a teacher should be able to detect a falling intonation from a rising intonation in his own voice as well as in a student’s. The success of learning does not only depend on the teacher but also involves the students’ awareness to learn English.